Effects of Administering Exogenous Bovine Somatotropin During the First Trimester of Pregnancy Altered Uterine Hemodynamics in Suckled Beef Cows - Sanford, Carla D.; Owen, Megan P. T.; McCarty, K.; Canal, Luara B.; Schulmeister, Tessa M.; Oosthuizen, Nicola; Fontes, Pedro L. P.; Lemley, Caleb O.; Bromfield, John J.; DiLorenzo, Nicolas; Lamb, G. Cliff (Frontiers in Animal Science, 2021)
The objective of this study was to examine the effects of recombinant bovine somatotropin (bST) administration on uterine hemodynamics and subsequent fetal programming in suckled cows during the first trimester of gestation. Crossbred beef cows (n = 152) were stratified by breed, days postpartum, parity, cyclicity status, and body condition score (BCS) before being assigned to either receive injections of bST every other week (BST; 500-mg/14 d) starting at fixed-time artificial insemination (TAI; d 0) until d 97 or to receive no bST (CTL). Blood samples were collected until d 97 for analysis of plasma concentrations of insulin-like growth factor 1 (IGF-1). Pregnancy was assessed via transrectal ultrasonography on d 41 and 173. A subset of pregnant cows (BST, n = 24; CTL, n = 28) were selected for doppler ultrasound assessment on d 97 and 233 of gestation. No differences (P = 0.99) were detected in body weight (BW) or BCS of dams; however, plasma concentrations of IGF-1 were greater (P < 0.001) in BST-treated cows. Color Doppler ultrasonography parameters differed whereby a treatment × day interaction (P = 0.007) was detected for RI on d 97 (P = 0.048); however, on d 233, resistance index did not differ (P > 0.10) but ipsilateral blood flow for BST-treated cows was greater (P = 0.0319) than controls. Mean heart girth diameter, crown-to-rump length, and neonate BW at 7 ± 5 d of calf age did not differ (P > 0.10). Liver tissue samples from each calf were collected for analysis of mRNA expression of target insulin-like growth factor system ligands. There was no difference in gene expression of hepatic IGF-1 between treatments (P = 0.99). A treatment × sex interaction was determined, where BST heifers had increased mRNA expression of IGFR1 compared to BST bulls (P = 0.03). Bi-weekly administration of bST until d 97 of pregnancy increased plasma concentrations of IGF-1, altered uterine hemodynamics in dams, induced sex-specific changes in liver gene expression of the offspring but failed to alter calf morphometries or calf performance until weaning.